Jurisdictional Disputes between Central and Local Governments in the Management of Coal Mining - Hartati Hartati; Zainal Amin Ayub (Faculty of Law, Sriwijaya University, Indonesia, 2024)
On June 10, 2020, President Joko Widodo ratified the amendment of Law Number 4 of 2009 to Law Number 3 of 2020 concerning Minerals and Coal, one of the substances that changed the rules of authority in granting licenses from initially located in the local government to the central government. Therefore, this study aims to analyse the issue of authority between the central government and local governments in coal mining management after the issuance of the Minerba Law in 2020. This research uses a qualitative approach using institutional data surveys as a data collection method. The collected data is analysed using descriptive analysis: data reduction, data presentation, and conclusion drawing. The findings in this study explain that in Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining, the authority of local governments is withdrawn to the central government, starting from Mining Business License (IUP), People's Mining License (IPR) and Special Mining Business License (IUPK), Special Mining Business License (IUPK), Rock Mining License (SIPB), Transfer Permit, Transportation and Sales Permit, Mining Service Business License (IUJP), and Sales IUP. Although all local government authorities are fully withdrawn from mining licensing, local governments can still carry out mining licensing if the central government delegates authority based on statutory provisions. This latest regulation emerged through the idea of the government together with the House of Representatives on the grounds of simplifying licensing by easing requirements to increase investment obtained by the state. However, this change makes it seem as if the government wants to return to the era of centralisation. It is contrary to the spirit of decentralisation and regional autonomy that is being embraced in Indonesia.